2019
DOI: 10.1002/btpr.2869
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma spore lipid protects mouse bone marrow mesenchymal stem cells and hematopoiesis from the cytotoxicity of the chemotherapeutic agent

Abstract: Cancer chemotherapeutic agents are frequently toxic to bone marrow and impair bone marrow functions. It is unclear whether ganoderma spore lipid (GSL) can protect bone marrow cells from the cytotoxicity of chemotherapy. To investigate the protective effects of GSL on bone marrow mesenchymal stem cells (MSCs) and hematopoiesis, we examined the effects of GSL on MSCs in vitro and hematopoiesis in vivo after treatment with the chemotherapeutic agent cyclophosphamide. MSCs and peripheral blood cells were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The Chinese medicine 2036 Specialty-Qiangxin recipe (2036S-QXR), consisting of three herb plant components, the Rhodiola rosea L. (Crassulaceae) extract, Ganoderma lucidum Karst (Ganodermataceae) spore powder, and grape seed proanthocyanidin extract, has been widely used as a health care product to improve cardiac function, prevent stroke, and strengthen the immune system. Our and other previous studies have shown the various therapeutic effects of Ganoderma lucidum spores (Zhang and Zeng 2004;Cheng et al 2007;Gao et al 2010;Zhou et al 2012;Pan et al 2019), the extract of Rhodiola rosea (Qu et al 2009;Roumanille et al 2020;Sun et al 2020), and grape seed extract (Zhang et al 2011;Huang et al 2020;Eid et al 2021). However, a systematic evaluation of the long-term toxicity of 2036S-QXR still remains unknown.…”
Section: Introductionmentioning
confidence: 60%
“…The Chinese medicine 2036 Specialty-Qiangxin recipe (2036S-QXR), consisting of three herb plant components, the Rhodiola rosea L. (Crassulaceae) extract, Ganoderma lucidum Karst (Ganodermataceae) spore powder, and grape seed proanthocyanidin extract, has been widely used as a health care product to improve cardiac function, prevent stroke, and strengthen the immune system. Our and other previous studies have shown the various therapeutic effects of Ganoderma lucidum spores (Zhang and Zeng 2004;Cheng et al 2007;Gao et al 2010;Zhou et al 2012;Pan et al 2019), the extract of Rhodiola rosea (Qu et al 2009;Roumanille et al 2020;Sun et al 2020), and grape seed extract (Zhang et al 2011;Huang et al 2020;Eid et al 2021). However, a systematic evaluation of the long-term toxicity of 2036S-QXR still remains unknown.…”
Section: Introductionmentioning
confidence: 60%
“…28,29 G. lucidum is one of the most well-known medicinal mushrooms and has been used for its therapeutic effects for more than 2,000 years. [31][32][33][34] GAs are the most significant secondary metabolites of G. lucidum and have many potential therapeutic applications, as claimed by numerous literature. 35,36 There is a considerable amount of researches that describes the influence of different parameters on growth and GA production of G. lucidum, such as optimization of fermentation conditions, elicitation, and molecular biology technique to achieve higher expression of GA biosynthesis-related genes.…”
Section: T a B L Ementioning
confidence: 99%
“…In the last two decades, numerous studies have explored the active components of G. lucidum and their biological effects along with underlying mechanisms of action 30 . To date, over 300 active compounds have been isolated from G. lucidum with numerous biological activities, including anti‐inflammatory, immune regulation, anti‐tumor, hepatoprotective, hypoglycemic, anti‐aging, neuroprotection, and antioxidant activities 31‐34 . GAs are the most significant secondary metabolites of G. lucidum and have many potential therapeutic applications, as claimed by numerous literature 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Proteins were extracted as previously described and separated by 10% sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) (Pan et al 2019), then being immunoblotted with a mAb against ER stress or cell cycle-related molecules, and visualized with an ECL kit (Pierce, Rockford, IL); b-actin was used as an internal control.…”
Section: Western Blottingmentioning
confidence: 99%